Pemberdayaan ibu PKK dalam pembuatan biopori berbasis limbah rumah tangga - Isna Rahma Dini; Fauza Azmimelwa; Joko Setiawan; Rachmad Saputra (Unri Conference Series: Community Engagement, 2020)
Various kinds of activities carried out by PKK mothers in filling their time working at home during the Covid-19 pandemic, one of which is farming around the yard. This farming activity certainly requires useful fertilizers to increase plant fertility. Biopores is an effort that can be made to improve soil health and trigger the natural decomposition of organic matter. The organic material used can come from kitchen waste. So far, biopores are known as an effort to overcome standing water and are still not widely used to increase soil fertility. This service aims to provide information on the manufacture and application of biopores in plants so that they can increase soil fertility in cultivated plants. The method used consists of lecturing methods, hands-on practice, and evaluating the achievement of activities using achievement measures. Based on the results of the posttest evaluation, there was an increase in the knowledge of PKK mothers about biopores, where initially only 40% increased to 100%. In addition, the direct practice of making and applying biopores carried out on one of the PKK mothers is an indicator of the high interest of PKK mothers in applying biopores. It can be concluded that community service activities are quite effective in increasing the ability and interest of PKK mothers in applying biopores to plants around their house yards.